Prevalência de aleitamento materno em crianças menores de um ano de idade em Feira de Santana - Reis, Mariana Ribeiro dos (2010)
Breastfeeding is recomended by Health Worldwide Organization like a lactante’s food, in the initial two years of life or more. Before this reality, the knowledge about the indicators of breastfeeding become necessary into the development and evaluation in relation to the actions of incentive to this practice. The purpose of this survey was to show the prevalence of breastfeeding in children under age in the city of Feira de Santana, Bahia in 2009, as well as to make up a profile of breastfeeding along thirteen years in the municipal district . A survey of transverse cutback where were interviewed 1471 mothers with children minor of one year of age in the second stage of the multivaccination campaign. The prevalence of breastfeeding n children minor of one year of age and of exclusive breastfeeding in children minor of six months of age was 76, 7% and 45, 4%, respectively. The varied analyses doubly demonstrate that low schooling (RP= 1,05%, IC: 95%: 1,00 – 1,10) and mothers that didn’t work out of their houses (RP= 1,62%,IC:95% : 1,49 – 1,77), were motherly features in which were associate a larger prevalence of breastfeeding in children minor of one year of age. In relation to exclusive breastfeeding, they demonstrate a significant association with larger prevalence in children minor of six months of age. The following characteristcs: mothers’sons that don’t work out of their houses, children, mothers’daughters that had many pregnancies, mothers’children with larger and equal age to 20 years old, not to use nursing bottle and dummy, to have born with a larger weight or equal to 2500 grams and to have suckled in the first day at home. The results demonstrate a positive growth in relation to the prevalence of breastfeeding in children minor of one year of age and a exclusive breastfeeding in children minor of six months of age, in 2009, when compared with the prevalence found in researches realized in 1996 and in 2001 in the municipal district.